Use of Platformer Educational Game Media in Increasing Knowledge About Calculus in Class VII and VIII Students of SMP Diponegoro Surabaya (study of class VII and VIII at SMP Diponegoro Surabaya) - Budiarti, Yashinta Dwi; Prasetyowati , Silvia; I. G. A. Kusuma Astuti N. P. (SURABAYA DENTAL THERAPIST JOURNAL, 2025)
Dental and oral hygiene is a condition in which a person’s oral cavity is free from dirt, such as plaque and calculus. Calculus is a collection of plaque that is calcified and adheres tightly to the surface of the teeth and other solid objects in the mouth, so that the teeth become rough and feel thick. Calculus that continues to be left in the mouth can cause irritation, inflammation of the gums and damage to the tissue supporting the teeth, and can cause the teeth to become loose and fall out by themselves. Research Problem of high calculus index in students of class VII and VIII at SMP Diponegoro. The aim of the research is to describe the description of knowledge about tartar after using educational platformer game media in students of class VII and VIII at SMP Diponegoro Surabaya City. This type of research is descriptive research. The target of this research was 45 respondents in class VII and VIII of SMP Diponegoro Surabaya. This research data collection method uses a questionnaire sheet. The results of this research showed that students’ knowledge about calculus before and after using platformer educational game media in class VII and VIII students at SMP Diponegoro Surabaya was in the poor to good category, after counseling was carried out.